Hubungan Kandungan Kimia Tanah terhadap Keanekaragaman Makrofauna Tanah pada Perkebunan Apel Semi Organik dan Anorganik - Nasirudin, Mohamad; Susanti, Ambar (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2018)
This study aims to determine the relationship of soil chemical content to soil macrofauna in semi-organic and inorganic apple plantations in Tulungrejo Village, Bumiaji District, Batu City. Observation of soil chemical properties carried out in the BPTP East Java laboratory. The soil was taken systematically on both fields. Observation of soil macrofauna is carried out by direct observation. The study was conducted in March - May 2018. The parameters observed in this study were soil (H ') macrofauna, and soil (pH, C-Organic, and N). The chemical content of soil in the semiorganic apple plantation is (pH = 7.8 C-Organic = 1.54 and N = 0.16), while the chemical content of soil in the land of inorganic apple plantations is (pH = 7 C-Organic = 0 , 5 and N = 0.06). The results of research on soil macrofauna in Semi Organic apple plantations found 9 orders consisting of 10 families and amounting to 247 individuals. The role of soil macrofauna includes 3 families and 45 individuals, 4 family detrivor and 42 individuals, and 3 family predators and 160 individuals. The results of research on soil macrofauna in the field of Inorganic found 8 orders, consisting of 9 families and numbered 162 individuals. The role of the soil macrofauna includes 3 families and 25 individuals, 3 families and 18 individuals, and 3 families and 119 individuals. Diversity index value (H') of soil macrofauna in semi-organic land is higher at 1.81, while in Inorganic land is 1.53.